A Systematic Evaluation of Six Different Physical Activity Routines: A Strategic Science Approach. Issue 1 (9th December 2021) - Taylor, Wendell C.; Bui, Chuong; Paxton, Raheem J.; Maity, Suman; Walker, Timothy J.; Robertson, Michael C.; Sadruddin, Shehla M.; Hare-Everline, Nicole; Craig, Derek W.
ABSTRACT: Physical inactivity and sedentary behaviors are major contributors to chronic diseases and premature mortality. Although the benefits of physical activity have been documented, no study has systematically evaluated the feasibility and satisfaction of different physical activity routines designed for workplace settings. Therefore, the objectives of this research were to develop and evaluate six different types of 15-min physical activity routines. Based on pilot testing, we developed six different physical activity routines designed for the 15-min break during the workday, and 12 dimensions were used to evaluate each routine. The dimensions were as follows: appropriateness of work attire, benefit, challenge, complexity, confidence, effort (i.e., physical), embarrassment, enjoyment, fatigue, flexibility, likability, and sweat (i.e., perspiration). Before completing the ratings, participants received definitions of each dimension. Ninety-four full-time employees participated in six routines (i.e., aerobic dance, ballet, Booster Break, circuit training, muscle strengthening, and yoga) and rated their experiences using a 5-point Likert scale immediately after each session. All routines received some favorable ratings and seemed acceptable as a workplace activity. Circuit training and aerobic dance ranked highest on challenge, complexity, effort (i.e., physical), embarrassment, fatigue, and sweat, and low on work attire appropriateness. Booster Break ranked relatively high on benefit, confidence, likability, and work attire appropriateness; moderate on fatigue; and low on sweat and embarrassment. Circuit training and aerobic dance routines were the most challenging and appropriate for workforces with employees who are physically active and/or prefer challenges. For workforces with a diversity of preferences, abilities, or new to physical activity routines, the Booster Break is recommended because it was rated favorably on all dimensions. Future research is recommended to replicate these findings and improve the implementation effectiveness of work break routines.